Tackling challenges in industrially relevant homogeneous catalysis: the Catalysis Research Laboratory (CaRLa), an industrial−academic partnership - Schaub, Thomas; Hashmi, A. Stephen K.; Paciello, Rocco (The journal of organic chemistry, 2019)
Abstract: Industrial–academic collaborations are broadly used for the development of new industrial processes. To achieve a strong and deep collaboration in the field of homogeneous catalysis, BASF and the Heidelberg University have been running the Catalysis Research Laboratory together in Heidelberg since 2006. This Perspective highlights the concept of this laboratory and our experiences over the past few years in this joint laboratory. How this collaboration works is explained in more detail using three selected projects: sodium acrylate based on CO2, the selective decomposition of cyclohexyl hydroperoxide to cyclohexanone, and the asymmetric amination of ketones with NH3/H2
Published online: October 1, 2018; Published in issue 19 April 2019
Gesehen am 29.05.2019